2022
DOI: 10.3389/fpls.2021.802016
|View full text |Cite|
|
Sign up to set email alerts
|

The LcKNAT1-LcEIL2/3 Regulatory Module Is Involved in Fruitlet Abscission in Litchi

Abstract: Large and premature organ abscission may limit the industrial development of fruit crops by causing serious economic losses. It is well accepted that ethylene (ET) is a strong inducer of organ abscission in plants. However, the mechanisms underlying the control of organ abscission by ET are largely unknown. We previously revealed that LcKNAT1, a KNOTTED-LIKE FROM ARABIDOPSIS THALIANA1 (KNAT1)-like protein, acted as a negative regulator in control of fruitlet abscission through suppressing the expression of ET … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…It is generally accepted that ethylene triggers IDA‐HAE/HSL2 signaling, which in turn accomplishes the last steps in the abscission process (Botton & Ruperti, 2019; Estornell et al., 2015; Li et al., 2021; Ma et al., 2022; Meir et al., 2019; Sto et al., 2015; Tucker & Yang, 2012; Wang et al., 2019; Wilmowicz et al., 2018; Ying et al., 2016). Previously, we found that LcACO2 , LcACS1 , and LcEIL3 are involved in litchi fruitlet abscission (Ma et al., 2019; Ma, Yuan, et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally accepted that ethylene triggers IDA‐HAE/HSL2 signaling, which in turn accomplishes the last steps in the abscission process (Botton & Ruperti, 2019; Estornell et al., 2015; Li et al., 2021; Ma et al., 2022; Meir et al., 2019; Sto et al., 2015; Tucker & Yang, 2012; Wang et al., 2019; Wilmowicz et al., 2018; Ying et al., 2016). Previously, we found that LcACO2 , LcACS1 , and LcEIL3 are involved in litchi fruitlet abscission (Ma et al., 2019; Ma, Yuan, et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, we observed that the expression of LcIDL1 was increased in LcDOF5.6‐silenced FAZ, and both LcIDL1 and LcHSL2 were decreased in LcRbohD‐silenced FAZ (Figure 8), suggesting that LcDOF5.6–LcRbohD‐mediated ROS has a positive effect on the LcIDL1‐LcHSL2 signaling in regulating the litchi fruitlet abscission. Considering that ethylene could also act upstream of IDA‐HAE/HSL2 signaling, which in turn accomplish the final stages of organ abscission (Botton & Ruperti, 2019; Ma et al., 2022; Meir et al., 2019), the activation of IDA signaling might be achieved by the ROS‐triggered ethylene signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Specific FaEIN3/EINs showed high expression levels at the initial red stage of the strawberry fruit in a certain cultivar, suggesting they might play a role during fruit ripening. Also, Ma et al [61,62] proposed that LcEIL2 and LcEIL3 regulated ethylene-activated litchi fruitlet abscission by binding to LcCEL2/8 and LcPG1/2 in a cell wall remodeling process and LcACS1/4/7 and LcACO2/3 in the ethylene biosynthetic pathway. Mu et al (2016) [57] demonstrated that the expression levels of most of the genes involved in ethylene biosynthesis and signaling had the same changing trend in non-climacteric fruits (grape and strawberry): they reached a maximum in the fruit development and then decreased, indicating that the mechanism of ethylene production and perception occurs in these fruits prior to ripening.…”
Section: Discussionmentioning
confidence: 99%
“…The development and functional exercise of the abscission layer is a complex and precise process in which multiple enzymes ( Tong et al, 2020 ; Wang et al, 2023 ), hormones ( Kućko, Wilmowicz & Ostrowski, 2019 ; Li et al, 2023 ), and genes ( Wang et al, 2021 ; Ma et al, 2022 ) are involved in regulation. Abscission is a physiological process associated with stress response and plant organ senescence.…”
Section: Introductionmentioning
confidence: 99%